2020
DOI: 10.5194/angeo-38-557-2020
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic noise absorption signature of particle precipitation during interplanetary coronal mass ejection sheaths and ejecta

Abstract: Abstract. We study here energetic-electron (E>30 keV) precipitation using cosmic noise absorption (CNA) during the sheath and ejecta structures of 61 interplanetary coronal mass ejections (ICMEs) observed in the near-Earth solar wind between 1997 and 2012. The data come from the Finnish riometer (relative ionospheric opacity meter) chain from stations extending from auroral (IVA, 65.2∘ N geomagnetic latitude; MLAT) to subauroral (JYV, 59.0∘ N MLAT) latitudes. We find that sheaths and ejecta lead frequently … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 102 publications
(130 reference statements)
1
4
0
Order By: Relevance
“…This conclusion agrees well with earlier observations of the radiation belt dynamics, where a 1-3 day delay was found between the substorm activity and the maximum radiation belt response (Forsyth et al, 2016). As was further discussed by Kilpua et al (2020), the direct substorm injection to the ionosphere results in less intense precipitation than that driven by wave-particle interaction, which is in effect when the injected electrons are drifting into the morning sector after the injection. It was also concluded by Grandin et al (2017) that strong CNA is more likely to occur during a substorm event with a longer duration.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This conclusion agrees well with earlier observations of the radiation belt dynamics, where a 1-3 day delay was found between the substorm activity and the maximum radiation belt response (Forsyth et al, 2016). As was further discussed by Kilpua et al (2020), the direct substorm injection to the ionosphere results in less intense precipitation than that driven by wave-particle interaction, which is in effect when the injected electrons are drifting into the morning sector after the injection. It was also concluded by Grandin et al (2017) that strong CNA is more likely to occur during a substorm event with a longer duration.…”
Section: Discussionsupporting
confidence: 92%
“…The CNA values during the substorms studied here peaked between 0.5 and 1.0 dB (Figure 4), which is between the longterm average CNA including the quiet times (CNA mainly below 0.5 dB, Kavanagh et al, 2004) and the absorption values related to geomagnetic storms driven by coronal mass ejection (CME) sub-structures, sheath and ejecta (CNA values typically around 1 dB, Kilpua et al, 2020). An earlier study on HSS-driven substorms reported CNA levels of 1-2 dB (Grandin et al, 2017).…”
Section: Discussionmentioning
confidence: 71%
“…A more direct estimate of the atmospheric impact area could be obtained by determining the spatial extent of the CNA, since this parameter is sensitive specifically to the particle precipitation energies associated with an atmospheric impact. Bland et al (2020) recently used the Super Dual Auroral Radar Network (Super-DARN, Lester, 2013) to estimate the spatial coverage of the particle precipitation impact area during pulsating aurora by studying the attenuation of 10-12 MHz radio noise in the Dregion ionosphere. They found that the atmospheric impact area extended over at least 4 • of magnetic latitude for 75 % of the PsA events studied, and 36 % of the events extended over at least 12 • of magnetic latitude.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous monitoring of energetic particle precipitation by riometers allows long-term global studies, such as statistical behaviour of solar proton and electron precipitation impact regions in the atmosphere (e.g. Kilpua et al 2020;Heino et al 2019;Heino and Partamies 2020). The two-dimensional CNA distribution, in turn, facilitates more detailed spatial distribution studies of hard precipitation regions in comparison with other observations (e.g.…”
Section: Climatology Of the Ionospherementioning
confidence: 99%
“…Some of the recent studies are listed in the next section. Kilpua et al (2020) studied electron precipitation associated with the interplanetary coronal mass ejections (ICME), i.e. the coronal mass ejection observed close to the Sun (CME) when it moves in the interplanetary space.…”
Section: Climatology Of the Ionospherementioning
confidence: 99%